Effects of Tetramethylpyrazine on Cardiac Function and Mortality Rate in Septic Rats - 郭力恒 杨澄 王磊 陈全福 胡亚南 张敏州 (Chinese journal of integrative medicine, 2012)
Objective： To study the effects of tetramethylpyrazine （TMP） on cardiac function and mortality rate in septic rats. Methods： Fifty male Sprague-Dawley rats were randomized into a sham-operation group （sham group, n=10）, normal saline group （NS group, n=20）, and TMP group （n=20）. The rats in the NS and TMP groups underwent cecal ligation and puncture （CLP） to induce sepsis. Rats in the NS group were injected with NS （10 mL/kg） immediately after CLP and 6 h after CLP. Rats in the TMP group were injected with TMP （10 mg/kg） at the same time points. Twenty-four hours after modeling, the mortality rates were observed in each group. Cardiac function and serum concentration of tumor necrosis factor α （TNF-α） were also tested. The correlation between TNF-α and the ejection fraction （EF） was observed. Left ventricle specimens were reserved for histomorphologic study. Results： Compared with the sham group, the NS and TMP groups had decreased EF values and increased mortality rates and serum TNF-α levels （P〈0.05）. The TMP group had a comparatively lower mortality rate and TNF-α level and a higher EF value compared with the NS group （P〈0.05）. Histomorphology indicated that myocardial inflammation in the TMP group was mild compared with that in the NS group. There was a negative correlation between TNF-α level and EF value （r=-0.583, P=0.000）. Conclusion： TMP could reduce the mortality rate of septic rats and had certain protective effects on cardiac function.